The Correlations Between Infectious Diseases, LBW History, and IMD with the Incidence of Stunting in Toddlers Aged 24-59 Months - Rahman, Prabowo; Mas'Odah, Siti; Sajiman; Aprianti (Jurusan Gizi Poltekkes Kemenkes Banjarmasin, 2026)
Stunting remains a national priority. The prevalence of stunting in Hulu Sungai Utara Regency remains above the RPJMN target of 18.37%. The highest number of stunting cases occurs in the 24-59 month age group, accounting for 70.5% of total cases. The combination of early childhood education, a history of low birth weight, and exposure to infectious diseases contributes to the high prevalence of stunting in toddlers aged 24-59 months. The purpose of this study was to determine the relationship between infectious diseases, a history of low birth weight, and early childhood education with stunting in toddlers aged 24-59 months in Kaludan Kecil Village, working area of Public Health Center Banjang. This research is an observational analytical study with a cross-sectional design and quantitative methods. The study was conducted in Kaludan Kecil Village, working area of UPT Public Health Center Banjang. The study sample consisted of mothers and toddlers aged 24–59 months, using a total sampling technique. The study was conducted from September to December 2025. Data were analyzed using the chi-square test and prevalence ratio. The analysis showed that 68.5% of toddlers had a history of infectious diseases, 83.3% did not experience low birth weight (LBW), 68.5% had a history of early breastfeeding (IMD), and 66.7% did not experience stunting. There was a relationship between infectious diseases (p=0.023, PR=3,692), a history of LBW (p=0.004, PR=3,184) and the incidence of stunting in toddlers aged 24-59 months. There was no relationship between a history of IMD and the incidence of stunting in toddlers aged 24-59 months (p=0.836). It is hoped that the Public Health Center can improve health programs to reduce the incidence of infectious diseases, such as increasing education on environmental hygiene and sanitation, conducting evaluations in reducing the incidence of low birth weight through prenatal classes, and socializing the importance of starting breastfeeding early to mothers.